FRI0112 Serum levels of IL-33 and SST2 are associated with functional disability in rheumatoid arthritis. (15th June 2017) - Pinto, MR; Kakehasi, A; Andrade, MV
Abstract : Background: Interleukin 33 (IL-33) is a cytokine related to amplification of the articular inflammation in rheumatoid arthritis (RA) animal models. Elevated IL-33 serum levels have been described in RA patients, suggesting a possible participation of this cytokine in the physiopathology of the disease. 1, 2 IL-33 soluble receptor (sST2) is a decoy receptor that functions as an inhibitor of the interaction of the transmembrane receptor with IL-33. 3 Objectives: To identify the association between serum levels of IL-33 and its soluble receptor (sST2) with clinical and laboratory characteristics of RA. Methods: Cross-sectional observational study in which RA patients were submitted to clinical and laboratorial evaluation. IL-33 and sST2 serum levels were measured by ELISA (R&D System Inc, Minneapolis, MN, USA). Results: 102 RA patients were included, 92, 5% women, mean age of 55, 5±10 years and mean disease duration of 17, 6±9, 5 years. Eighty-four (82, 4%) patients had seropositive RA. The median (interquartile range) IL-33 serum level was 69.1 pg/ml (31.6 - 114.5). Higher scores on the visual analogue scale (VAS) of disease activity assessed by the examiner were associated with higher IL-33 values (CI95%: 0.01–0.05). In the group of patients with high titres of rheumatoid factor (RF), IL-33 levels were higher, compared to the group with negative RF (95% CI: 0.55 - 2.34). In 34 (33.3%) patients, IL-33 was undetectable and the presence of metabolic syndrome 4 represented a 63% lower chance (OR =0.37, 95% CI: 0.15–0.90) of having IL-33 detected. In addition, 1-unit increase in HAQ-DI increased by 2.43 times the chance of detecting IL-33 (95% CI: 1.23 - 4.80). The median sST2 serum level was 469.8 pg/ml (336.3–651). sST2 was associated with worse functional capacity by the classification of Steinbroker 5 (IC95%: 0.09 - 0.5), use (current or in the past) of tobacco (95% CI: 0.02 - 0.53) and use of leflunomide (95% CI: 0.05 - 0.53). There was no correlation between IL-33 and sST2 levels. Conclusions: These findings may suggest that both IL-33 and its soluble receptor play a role as a marker of RA severity and functional disability. The negative association of IL-33 with metabolic syndrome is in agreement with the possible protective role of this cytokine in relation to lipid metabolism. 6 References: Xu D, Jiang HR, Li Y, et al. IL-33 exacerbates autoantibody-induced arthritis. J Immunol. 2010;184(5):2620–2626. Matsuyama Y, Okazaki H, Tamemoto H, et al. Increased levels of interleukin 33 in sera and synovial fluid from patients with active rheumatoid arthritis. J Rheumatol. 2010;37(1):18–25. Schmitz J, Owyang A, Oldham E, et al. IL-33, an interleukin-1-like cytokine that signals via the IL-1 receptor-related protein ST2 and induces T helper type 2-associated cytokines. Immunity. 2005;23(5):479–490. Alberti KG, Zimmet P, Shaw J. Metabolic syndrome–a new world-wide definition. A Consensus Statement from the International Diabetes Federation. Diabet Med. 2006;23(5):469–480. Steinbrocker O, Traeger CH, Batterman RC. Therapeutic criteria in rheumatoid arthritis. JAMA 1949;140:659–62. Kunes P, Holubcová Z, Kolácková M, Krejsek J. The counter-regulation of atherogenesis: a role for interleukin-33. Acta Medica (Hradec Kralove). 2010;53(3):125–129. Disclosure of Interest: None declared